Chronological conundrums : Egypt and the Middle Bronze Age Southern Levant - Höflmayer, Felix (Journal of ancient Egyptian interconnections ;, 2017)
INTRODUCTIONChronological Conundrums: Egypt and the Middle Bronze Age Southern Levant Felix Hoeflmayer, Susan L. CohenARTICLESRadiocarbon Evidence from Tell Abu-en-Ni'aj and Tell el-Hayyat, Jordan, and Its Implications for Bronze Age Levantine and Egyptian Chronologies Steven E. Falcomer, Patricia L. FallA Radiocarbon Chronology for the Middle Bronze Age Southern Levant Felix HoeflmayerReevaluation of Connections Between Egypt and the Southern Levant in the Middle Bronze Age in Light of the New Higher Chronology Susan L. CohenThe Absolute Chronology of the Middle Bronze Age Palace at Tel Kabri: Implications for Aegean-Style Wall Paintings in the Eastern Mediterranean Eric H. Cline, Assaf Yasur-Landau, Andrew KohDjehutihotep and Megiddo in the Early Middle Bronze Age Matthew J. AdamsA Maximalist Interpretation of the Execration Texts-Archaeological and Historical Implications of a High Chronology Katharina StreitThe Course of 14C Dating Does Not Run Smooth: Tree-Rings, Radiocarbon, and Potential Impacts of a Calibration Curve Wiggle on Dating Mesopotamian Chronology Sturt Manning, Gojko Barjamovic, Brita Lorentzen